Augustianizm Benedykta XVI a oddolna nauka społeczna Kościoła - Hordecki, Bartosz (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
For several decades Joseph Ratzinger has been an influential co-architect of the grass-roots social teaching of the Church. Since his nomination as the Prefect of the Congregation for the Doctrine of the Faith he has also become one of the most important demiurges of the top-down sources of this teaching. J. Ratzinger, or Pope Benedict XVI, compared himself to a ‘pack donkey’, who faithfully and persistently follows Christ. It seems that making reference to Bishop Hippona, the Bishop of Rome excessively underestimates the perversity of ‘God’s sheep’ listening to him. The works of J. Ratzinger lack appealing warnings against the theopolitical reception of Augustian thought.